A Study of Body Proportions of the Elderly with Mobility Constraints - AMPHAIPHAN, UKRIT (Princess of Naradhiwas University Journal, 2023)
This project intended to examine the elderly’s health data, body proportions, hand pressure capacity, to build prototypes of assistive devices for the elderly with limited mobility, and to study the effectiveness of the prototype. The sample group consisted of senior people in Nakhon Pathom Province who were at least 60 years old and had mobility issues; however, they could carry out basic daily tasks on their own. The statistics used for data analysis were frequency, percentage, mean, and standard deviation. The findings revealed that 90 percent of the older individuals had improper walking posture (sitting-walking inside and outside the home) as follows: 20 percent had movement defects such as spasms; 40 percent were unable to stand stable by themselves; 50 percent were unable to walk by themselves; and 60 percent had muscle weakness, knee pain and knee osteoarthritis (OA). From the preliminary data, this study focused on finding guidelines for product design to build prototypes of assistive devices for the elderly with limited mobility. The measurement elbow height has an average of 108.46(±1.07), hip width with an average of 50.70(±0.79) and weight (Kilograms) has an average of 76.96(±2.04), and a finger test average was 30.56(±6.26). The measurement of body dimensions based on ergonomics was considered in product design. The study also investigated the effectiveness of the assistive device which revealed that the suitability of the utility was at a high level (X= 4.13, S.D. = 0.34), the security was at the highest level (X= 4.30, S.D. = 0.46), and the strength was at a high level (X= 4.20, S.D. = 0.65).